BOOMERanG: a scanning telescope for 10 arcminutes resolution CMB maps - Masi, S.; Ade, P. A. R.; Artusa, R.; Bock, J. J.; Boscaleri, A.; Crill, B. P.; de Bernardis, P.; De Troia, G.; Farese, P. C.; Giacometti, M.; Hristov, V. V.; Iacoangeli, A.; et al. (arXiv, 1999)
The BOOMERanG experiment is a stratospheric balloon telescope intended to measure the Cosmic Microwave Background anisotropy at angular scales between a few degrees and ten arcminutes. The experiment features a wide focal plane with 16 detectors in the frequency bands centered at 90, 150, 220, 400 GHz, with FWHM ranging between 18 and 10 arcmin. It will be flown on a long duration (7-14 days) flight circumnavigating Antarctica at the end of 1998. The instrument was flown with a reduced focal plane (6 detectors, 90 and 150 GHz bands, 25 to 15 arcmin FWHM) on a qualification flight from Texas, in August 1997. A wide (~300 sq. deg, i.e. about 5000 independent beams at 150 GHz) sky area was mapped in the constellations of Capricornus, Aquarius, Cetus, with very low foreground contamination. The instrument was calibrated using the CMB dipole and observations of Jupiter. The LDB version of the instrument has been qualified and shipped to Antarctica. : 12 pages, 9 figures